Music in Liquid Forms: A Framework for the Creation of Reactive Music Recordings - HENNIGAN, KEITH (Trinity College Dublin. School of Creative Arts. Discipline of Music, 2018)
This thesis aims to research and propose a possible framework or model for the creation and dissemination of liquid music recordings, defining this term in relation to others such as reactive, generative and so on. Results will include the establishment of a sound theoretical basis for liquid music creation, a three-stage creation model, and practical demonstrations of the research for illustrative purposes. A full discussion of liquid music as it currently exists, in any genre or medium, must be undertaken to establish precedents and the current state of the field. This thesis focuses on liquid music recordings, rather than live performance or installation works; furthermore, it takes popular music as a focus for production and aesthetics. This is due priamrily to the pivotal role of the recording in popular music. Definitions of key terms related to liquid music will be drawn from the surrounding literature, and boundaries between classifications of reactive works that include audio will be established. Video game audio, as a field in which reactive systems have been employed for decades with greater sophistication than anywhere else, will be discussed at length as part of the research. Theoretical and practical approaches to video game music may often be equally applicable to liquid music works, separated from any narrative or ludic context. The technology for music production, with regards to both established music production and tools for reactive music, will be discussed. Finally, a number of demonstration works will be created in order to demonstrate the feasibility of the proposed creation model. These works will utilize a variety of compositional approaches, technological choices and interface methods, to highlight the adaptability of the model.
APPROVED
Keywords: Interactive music; Reactive music; Generative music; Procedural audio